Persepsi Gen Z Terhadap Keputusan Karir Pada Mahasiswa Ilmu Komunikasi Universitas Mulawarman (Studi Fenomenologi Pemilihan ASN) - Frenita Virgo Simanullang; Johantan Alfando W S; Silviana Purwanti; Ziya Ibrizah (Professional: Jurnal Komunikasi dan Administrasi Publik, 2026)
Choosing a career is an important decision that shapes one’s future. Currently, civilservice is considered a promising profession because it offers long-term benefits such asa guaranteed pension and other allowances. This study aims to understand theperceptions of Gen Z—specifically, Communication Studies students at MulawarmanUniversity—regarding the decision to pursue a career in civil service. This study employsa qualitative method with a phenomenological approach to explore individual meaningsand experiences. This study applies DeVito’s Perception Theory and employs datacollection techniques such as observation, interviews, and documentation, utilizingCreswell’s data analysis techniques as the analytical method. The results indicate thatGen Z’s—specifically Communication Studies students’—perceptions of the civil serviceprofession are shaped by their interpretation of it as a symbol of life stability amid theeconomic uncertainty of the creative industry. The civil service profession is not seen asan obstacle to creativity but rather as a stable environment that allows for work-lifebalance, ensuring that life and work remain in harmony. The civil service is considered apromising profession because it offers career progression and the assurance of a brightfuture.